Post-Pulmonary Embolism Syndrome and Functional Outcomes after Acute Pulmonary Embolism - Luijten, Dieuwke; de Jong, Cindy M. M.; Ninaber, Maarten K.; Spruit, Martijn A.; Huisman, Menno V.; Klok, Frederikus A. (Seminars in Thrombosis and Hemostasis, 2022)
Survivors of acute pulmonary embolism (PE) are at risk of developing persistent, sometimes disabling symptoms of dyspnea and/or functional limitations despite adequate anticoagulant treatment, fulfilling the criteria of the post-PE syndrome (PPES). PPES includes chronic thromboembolic pulmonary hypertension (CTEPH), chronic thromboembolic pulmonary disease, post-PE cardiac impairment (characterized as persistent right ventricle impairment after PE), and post-PE functional impairment. To improve the overall health outcomes of patients with acute PE, adequate measures to diagnose PPES and strategies to prevent and treat PPES are essential. Patient-reported outcome measures are very helpful to identify patients with persistent symptoms and functional impairment. The primary concern is to identify and adequately treat patients with CTEPH as early as possible. After CTEPH is ruled out, additional diagnostic tests including cardiopulmonary exercise tests, echocardiography, and imaging of the pulmonary vasculature may be helpful to rule out non-PE–related comorbidities and confirm the ultimate diagnosis. Most PPES patients will show signs of physical deconditioning as main explanation for their clinical presentation. Therefore, cardiopulmonary rehabilitation provides a good potential treatment option for this patient category, which warrants testing in adequately designed and executed randomized trials. In this review, we describe the definition and characteristics of PPES and its diagnosis and management.
Keywords: pulmonary embolism; cardiopulmonary rehabilitation; pulmonary hypertension; patient-reported outcome measures; echocardiography